Posizionamento sotto copertura arborea: il CFS presenta il progetto TARGET-STARS - Pititto, Gianluca (GEOmedia, 2009)
GPS positioning under vegetation coverage: the italian National Forest Corps presents the TARGET-STARS project The project TARGET-STARS has been officially presented last june 30th, during a conference held at the italian Department of Food, Agriculture and Forest. TARGET-STARS aims to create a network of geodetic points inside particular areas defined by a huge vegetation coverage. This network will be useful for users who need to correct their positioning data in those areas, avoiding the errors caused by multipath.